Weekly trends in emergency department visits, hospitalizations, and mortality in patients with end-stage kidney disease: nationwide registry analysis - Hye Eun Yoon; AJin Cho; Seon A. Jeong; Wookjin Choi; Dai Hai Choi; Hayne Cho Park; Jung Eon Kim; Young-Ki Lee; Kyung Don Yoo (PLoS ONE, 2026)
Patients with end-stage kidney disease (ESKD) undergoing thrice-weekly hemodialysis may experience higher mortality rates following their longest dialysis-free interval. However, information on weekly patterns of emergency department (ED) visits and outcomes in patients with ESKD compared with those without chronic kidney disease (CKD) is limited. We aimed to examine ED visit patterns among patients with ESKD throughout the week in the Republic of Korea and assess whether weekend admissions correlate with higher ED utilization and mortality rates. To this end, we retrospectively analyzed data from the National Emergency Department Information System in the Republic of Korea from January 2018 to December 2021. ED visits, hospitalizations, and in-hospital mortality were assessed daily. Logistic regression analyses were used to adjust for demographic and clinical factors, including the Korean Triage and Acuity Scale. Overall, 159,456 ED visits by patients with ESKD and 21,547,014 ED visits by those without CKD were included. Compared with the non-CKD group, patients with ESKD were older, mostly men, and presented with more severe conditions at ED admission. A distinct weekly pattern emerged among patients with ESKD, with the highest ED visit rates on Mondays (19.9%) and Tuesdays (15.8%), whereas those with non-CKD most frequently visited on Sundays (19.1%) and Saturdays (16.2%). Hospitalization rates were substantially higher among patients with ESKD (66.5%) than among those with non-CKD (21.3%), peaking on Wednesdays (67.2%) and Thursdays (67.4%). Moreover, patients with ESKD had a higher in-hospital mortality rate (9.2%) than those without CKD (5.1%), particularly on Wednesdays (9.7%) and Thursdays (9.4%). Our findings indicate that patients with ESKD exhibit pronounced weekly patterns in ED visits, hospitalizations, and mortality compared with those without CKD. Notably, ED visits among patients with ESKD were highest on Mondays and Tuesdays, whereas hospitalization and mortality rates peaked on Wednesdays and Thursdays.